Schaum's outline of basic electricity - Gussow, Milton. (New York : McGraw-Hill)
'Basic Electricity' delivers a grounding in electricity to technicians in a wide range of fields, including computer repair, telephone installation and repair, and auto mechanics. It includes new chapters along with new sample problems.